Neuronal correlates of asocial behavior in a BTBR T+Itpr3tf/J mouse model of autism - Meyza, Ksenia; Nikolaev, Tomasz; Kondrakiewicz, Kacper; Blanchard, D. Caroline; Blanchard, Robert J.; Knapska, Ewelina (Frontiers in Behavioral Neuroscience, 2015)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder characterized, in part, by an inability to adequately respond to social cues. Patients diagnosed with ASD are often devoid of empathy and impaired in understanding other people’s emotional perspective. The neuronal correlates of this impairment are not fully understood. Replicating such behavioral phenotype in a mouse model of autism would allow us an insight into the neuronal background of the problem. Here we tested BTBR T+Itpr3tf/J (BTBR) and c57BL/6J (B6) mice in two behavioral paradigms: The Transfer of Emotional Information test and the Social Proximity test. In both tests BTBR mice displayed asocial behavior. We analyzed c-Fos protein expression in several brain regions after each of these tests, to find that, unlike B6 mice, BTBR mice react to a stressed cagemate exposure in the Transfer of Emotional Information test with no increase of c-Fos expression in either the prefrontal cortex or the amygdala. After Social Proximity exposure however, we observed a strong increase in c-Fos expression in the CA3 field of hippocampus and two hypothalamic regions of BTBR brains. This response was accompanied by a strong activation of periaqueductal regions related to defensiveness, which suggests that BTBR mice find unavoidable social interaction highly aversive.